Fishes of the genus Lutianus off the East African coast and Part 2: Notes on the biology of the Lutjanids of the East African coast - Talbot, Frank Hamilton (Department of Biological Sciences, 2020)
While investigating the biology of the economically important members of the genus Lutianus on the East African coastline, difficulty was experienced with the identification and the nomenclature of the group using existing literature. It was essential that adequate descriptions of the species of the genus should be available before their biology could be investigated. Routine work of the East African Marine Fisheries Research Organization has produced over 1,000 specimens for study. The Organization's vessel, the M.V. "Research", has collected by handlines, multiple trolling lines, gill nets, deep lines and basket traps over the six hundred mile coastline of Kenya, Tanganyika and Zanzibar Protectorate, i.e. from Lat. l o 30" S. to 10° 30" S. This material forms the basis of the present paper. Underwater observations with and without a Seibe-Gorman aqualung down to seven fathoms have been made on a number of coral reefs. In this way some knowledge of the habits of certain species of the genus has been acquired, and some species rarely taken by normal fishing methods were discovered to be common. Specimens of these have been collected by spear guns. Where notes of habits of a species have been made they have been appended under the heading "Ecological note". Of the thirteen species of the genus found in the area, all (except the very small L. ehrenbergi) pass through the local markets and are considered good eating, and seven are important food fishes. Economically the genus ranks as one of the three most important groups of bottom Telcosts; the others being the Epinephelids and the genus Lethrinus.